Project-Based Learning Model Based on Sasak Local Wisdom in Tourism Geography Subjects to Enhance Critical Thinking Skills - Syafril; Mas’ad (Universitas Pendidikan Ganesha, 2025)
Critical thinking skills are essential competencies in 21st century education, but they are often underdeveloped in geography learning due to the lack of contextualized learning approach. In addition, the lack of integration of local wisdom values in the learning model contributes to the low involvement and meaning of students to the material. This study aims to develop a Project-Based Learning (PjBL) learning model based on Sasak local wisdom to improve students' critical thinking skills in Tourism Geography subjects. The research used a Research and Development (R&D) approach modified from the Borg & Gall model. Data collection techniques include expert validation, limited trials, and critical thinking tests. The results of expert validation showed that the model had a very good level of feasibility with an average percentage of feasibility above 90%. Meanwhile, the critical thinking test results showed a significant increase from the pre-test average score of 62.40 to 84.20 in the post-test. These findings indicate that the application of the Sasak local wisdom-based PjBL model is able to improve students' critical thinking skills through a contextual, collaborative, and culture-based approach. The results of this study have implications for enriching the types of geography learning methods that are oriented toward strengthening local values and developing 21st-century skills.